Effect of complementary food with small amounts of freshwater fish on whole blood n-3 fatty acids in Cambodian infants age 6–15 months. (August 2018) - Nurhasan, Mulia; Roos, Nanna; Skau, Jutta KH; Wieringa, Frank T; Friis, Henrik; Michaelsen, Kim F; Dijkhuizen, Marjoleine A; Stark, Ken D; Ritz, Christian; Chhoun, Chamnan; Lauritzen, Lotte
Highlights: Small amounts of freshwater fish had no impact on infants' n-3 LCPUFA status. Fish-based foods reduced n-6 PUFA and n-6/n-3 PUFA ratio in non-breastfed infants. Late cessation of breastfeeding positively correlated with infants' n-3 LCPUFA. Cambodian infants' FA status was better compared to children in developed high-income countries. Abstract: The impact of freshwater fish consumption on the status of long-chain n-3 fatty acids (n-3 LCPUFA) in infants in landlocked, low-income populations is unknown. We used secondary data from a randomized, single-blinded, controlled trial to evaluate the impact of daily consumption of complementary food products with small amounts of freshwater fish on whole blood n-3 LCPUFA in Cambodian infants. Infants (n = 419), received daily, one of four food products for 9 months. Two products contained freshwater fish: WinFood (10% fish by dry weight) and WinFood-L (12% fish by dry weight), while two products were non-fish-based: corn-soy blends (CSB+ and CSB++). Whole blood fatty acids and breastfeeding status were assessed at baseline and endline of the intervention. The WinFood products contributed to an estimated maximum intake of 86.5 mg/day n-3 LCPUFA. There was no difference in whole blood n-3 LCPUFA among the four intervention groups or between the fish-based and the non-fish-based groups (p ≥ 0.142). At endline, 71% of the children were still breastfed. Interaction analyses indicated a lower ratio of n-6/n-3 PUFA in non-breastfed infants in the WinFood groups compared to the CSB groups (pinteraction = 0.026). Thus, a high intake of n-3 LCPUFA from breastmilk may have blurred a potential impact of small amounts of freshwater fish effect on n-3 LCPUFA status in Cambodian infants.